Chronic Medication Use in Children Insured by Medicaid: A Multistate Retrospective Cohort Study - Feinstein, James A; Hall, Matt; Antoon, James W; Thomson, Joanna; Flores, Juan Carlos; Goodman, Denise M; Cohen, Eyal; Azuine, Romuladus; Agrawal, Rishi; Houtrow, Amy J; DeCourcey, Danielle D; Kuo, Dennis Z; et al. (Pediatrics (Evanston), 2019)
Little is known about the use of chronic medications (CMs) in children. We assessed the prevalence of CM use in children and the association of clinical characteristics and health care resource use with the number of CMs used. This is a retrospective study of children ages 1 to 18 years using Medicaid from 10 states in 2014 grouped by the annual number of CMs (0, 1, 2-4, 5-9, and ≥10 medications), which are defined as a dispensed ≥30-day prescription with ≥2 dispensed refills. Trends in clinical characteristics and health care use by number of CMs were evaluated with the Cochran-Armitage trend test. Of 4 594 061 subjects, 18.8% used CMs. CM use was 44.4% in children with a complex chronic condition. Across all children, the most common CM therapeutic class was neurologic (28.9%). Among CM users, 48.8% used multiple CMs (40.3% used 2-4, 7.0% used 5-9, and 0.5% used ≥10). The diversity of medications increased with increasing number of CMs: for 1 CM, amphetamine stimulants were most common (29.0%), and for ≥10 CMs, antiepileptics were most common (7.1%). Of $2.3 billion total pharmacy spending, 59.3% was attributable to children dispensed multiple CMs. Increased CM use (0 to ≥10 medications) was associated with increased emergency department use (32.1% to 56.2%) and hospitalization (2.3% to 36.7%). Nearly 1 in 5 children with Medicaid used CMs. Use of multiple CMs was common and correlated with increased health care use. Understanding CM use in children should be fundamentally important to health care systems when strategizing how to provide safe, evidence-based, and cost-effective pharmaceutical care to children.